Waste press mud in enhancing the performance of glass powder blended cement. (27th December 2021) - Radwan, Mohammed K.H.; Mo, Kim Hung; Onn, Chiu Chuen; Ng, Chee Guan; Ling, Tung-Chai
Highlights: Feasibility of using press mud in glass powder blended cement was examined. Ternary cements with 10–15% press mud + 20% glass powder give promising performance. Presence of press mud facilitates reaction of glass powder to provide more hydration products. Abstract: Due to the significant environmental damages caused by cement production, the use of blended cement has gained greater attention. This paper explores the novel use of solid waste from the sugar industry namely press mud (PM) and waste glass powder (GP) as cement replacement in ternary blended cement. The ternary blended cement consists of 20% GP and the influence of PM at various cement replacement levels between 5 and 20% was investigated. The fresh, strength, sorption, morphological, and thermogravimetric characteristics of the ternary blended cements were evaluated. The results showed that the incorporation of 10% and 15% of PM could improve the consistency, early and later age strengths, exhibit similar flexural strength and reduce the sorptivity of the GP binary cement mortar. The morphologies were also observed to have improved by reducing of voids, facilitating reaction of GP particles, and contributing additional hydration products. This was confirmed by thermogravimetric analysis results, whereby more hydration products were found in cement-GP-PM ternary cement pastes. In overall, the suitable integration of PM could improve the properties of ternary blended cement containing GP while reducing the usage of cement.